Analisis Usahatani Penangkaran Benih Kedelai (Kasus di Subak Kusamba, Kecamatan Dawan, Kabupaten Klungkung) - I KETUT SUARDANA; I GUSTI AGUNG AYU AMBARAWATI; I DEWA PUTU OKA SUARDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract National seedling has been running for 30 years, but the availability of qualified seed is not enough. This is an opportunity for soybean seed breeding at Subak Kusamba to supply soybean seed, especially for Klungkung regency. The research objective in this study is to determine income generated from soybean seed farming received by farmers and the constraints faced in farming. This study was conducted at Subak Kusamba, Dawan sub district, Klungkung. Samples were selected from all 25 farmers participated in the farming of soybean seed. Methodology in this study includes descriptive qualitative, farming analysis and Revenue/Cost (R/C) ratio. Results showed that the income received by farmers was Rp 2,191,885.84 for an average of 34,08 are of land for one growing season. The R/C ratio was 3.07, implying that soybean seed farming is beneficial. Constraints faced by farmers were decreased rainfall in 2014 which affected the activity and productivity of soybean. Due to the lack of water availability, it is suggested to develop water reservation, especially during dry season by developing water tanks or other irrigation systems technology. To reduce variable costs, it can be done through the use of organic fertilizer or compost, superior seeds and soybean harvesting machines. Keyword: seed breeding, soybean, farm analysis